EAACI position statement on asthma exacerbations and severe asthma. Issue 12 (6th November 2013) - Custovic, A.; Johnston, S. L.; Pavord, I.; Gaga, M.; Fabbri, L.; Bel, E. H.; Le Souëf, P.; Lötvall, J.; Demoly, P.; Akdis, C. A.; Ryan, D.; Mäkelä, M. J.; et al.
Abstract Asthma exacerbations and severe asthma are linked with high morbidity, significant mortality and high treatment costs. Recurrent asthma exacerbations cause a decline in lung function and, in childhood, are linked to development of persistent asthma. This position paper, from the European Academy of Allergy and Clinical Immunology, highlights the shortcomings of current treatment guidelines for patients suffering from frequent asthma exacerbations and those with difficult‐to‐treat asthma and severe treatment‐resistant asthma. It reviews current evidence that supports a call for increased awareness of (i) the seriousness of asthma exacerbations and (ii) the need for novel treatment strategies in specific forms of severe treatment‐resistant asthma. There is strong evidence linking asthma exacerbations with viral airway infection and underlying deficiencies in innate immunity and evidence of a synergism between viral infection and allergic mechanisms in increasing risk of exacerbations. Nonadherence to prescribed medication has been identified as a common clinical problem amongst adults and children with difficult‐to‐control asthma. Appropriate diagnosis, assessment of adherence and other potentially modifiable factors (such as passive or active smoking, ongoing allergen exposure, psychosocial factors) have to be a priority in clinical assessment of all patients with difficult‐to‐control asthma. Further studies with improved designs and new diagnostic tools are needed to properly characterize (i) the pathophysiology and risk of asthma exacerbations, and (ii) the clinical and pathophysiological heterogeneity of severe asthma.